Research on the Orderliness Synergy Between Conventional and Nonconventional for Energy Transition in China - Liu, Pingkuo; Lu, Cunyu; Zhao, Ruiqi (Frontiers in Energy Research, 2022)
Many industrialized countries are pursuing energy transition, but their focuses are different. The Orderliness-Synergy as a unique aspiration of the current energy transition is emphasized in this paper by constructing an Orderliness-Synergy Evaluation Model and selecting a dataset covering the period of 2011-2018 from Industrial Scale, Economic Benefit, Social Contribution as well as Growth Potential of China to calculate the Comprehensive Development Level and the Orderliness-Synergy Degree of both the conventional energy industry and the non-conventional one. A novel evaluation model with stock-increment attributes is built to measure the resource storage and the growth rate systematically and to further analyze their driving forces. The results reveal that: (1) The overall Orderliness-Synergy Degree of those two sub-industries shows an upward trend year by year, however, there are some significant differences among them. (2) China’s Energy transition has shown a dramatic promotion in structural upgrading, while the momentums of those two sub-industries show a shift from the stock-resource-contribution advantage to the increment-resource-contribution advantage. (3) The actual stock-increment contribution coefficient values of those two sub-industries have not reached the development expectations of industrial performances, and there is still reasonable space for structural optimization. Finally, policy implications are discussed.